Carotid Intima-Media Thickness and Lipid Profile in Children With Kawasaki Disease: A Single-Center Follow-up Study After a Mean Duration of 6.9 Years. Issue 7 (October 2018) - Gopalan, Kavitha; Singh, Surjit; Vignesh, Pandiarajan; Gupta, Anju; Rohit, Manojkumar; Attri, Savita Verma
Abstract : Background: Kawasaki disease (KD) has a predilection to involve coronary arteries, leading to several long-term cardiovascular sequelae. Apart from coronary artery abnormalities, children with KD are also prone to develop premature atherosclerosis, endothelial dysfunction, and lipid abnormalities. Some of these complications may occur even in children who have received appropriate treatment with intravenous immunoglobulin in the acute phase. Methods: In 2009, we had studied carotid intima-media thickness (cIMT) and lipid profile in 27 children with KD at least 1 year after the acute episode. In the present study, we have followed up the same cohort of 27 children at least 5 years after the acute episode of KD. We measured the cIMT, a surrogate marker for premature atherosclerosis, and fasting lipid profile in the cohort and compared the results with values obtained in our previous study. Results: There was significantly higher mean cIMT in children with KD as compared with control subjects. However, there was no significant difference in cIMT among children in the cohort at 1 and 5 years of follow-up. Abnormal lipid profile was seen in 7 of 27 children in the present study, 5 of whom also had had lipid abnormality at 1-year follow-up. This suggests that lipid abnormalities in KD may be long lasting. Conclusions: Children with KD need careful long-term follow-up even when they do not have overt and persistent coronary artery abnormalities. It is possible that consequences of KD in childhood may impact health status of young adults several years later.